District Central Libraries in Rayalaseema Region of Andhra Pradesh: A Study - Raghavaiah, Parvathaneni; Babu, K. Surendra (DESIDOC Journal of Library & Information Technology, 2017)
This paper focuses on the functioning, library resources, services, and problems existing in the District Central Libraries of Rayalaseema region of  Andhra Pradesh. A survey was conducted using questionnaire tool for collecting data from the librarians of the District Central Libraries (DCL) regarding collection development, sources of grants, manpower, library services, physical and ICT infrastructural facilities, etc. The study reveals that majority of the libraries are possessing the collection in the range of 40,000 to 50,000. Further, it is also found that lack of staff, ICT facilities, lack of sufficient budget are the main problems faced by these libraries in Rayalaseema region.